1975
DOI: 10.1021/j100590a010
|View full text |Cite
|
Sign up to set email alerts
|

Viscosities and partial molal volumes of some tetramethylcarboxamides at 25.deg.

Abstract: The viscosities and densities of four tetramethyldicarboxamides, tetramethylpimelamide, tetramethylazelamide, tetramethylsuberamide, and tetramethylsebacamide, were measured throughout the entire aqueous solubility range of these compounds at 25°C. An interesting feature of the partial molal volume behavior patterns of the amides is the presence of a minimum in the partial molal volume and a maximum in viscosity occurring at definite integral mole fractions for the odd C homologs, tetramethylpimelamide and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The properties of carboxamides have been the subject of considerable Interest because of the versatility of these compounds as solvents and their close relationship to peptides and proteins. Densities and viscosities of aqueous mixtures of several carboxamides have been determined to gain insight into the interactions in these systems (1)(2)(3)(4)(5). Surprisingly there have been practically no systematic studies on the density and viscosity behavior of mixtures of these amides with cosolvents other than water.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of carboxamides have been the subject of considerable Interest because of the versatility of these compounds as solvents and their close relationship to peptides and proteins. Densities and viscosities of aqueous mixtures of several carboxamides have been determined to gain insight into the interactions in these systems (1)(2)(3)(4)(5). Surprisingly there have been practically no systematic studies on the density and viscosity behavior of mixtures of these amides with cosolvents other than water.…”
Section: Introductionmentioning
confidence: 99%
“…Materials-The tetramethyl-substituted dicarboxamides were prepared according to a previously reported procedure (2). The purity of the amides was determined by vapor phase chromatography, and the conductivity of aqueous amide solutions was checked by the method described previously (10).…”
Section: Methodsmentioning
confidence: 99%
“…The solvent properties of amides are attributed in part to the strong dipole of the amide function and to the good electron-donating properties of the carbonyl group. Recent studies on a series of tetramethyl-substituted dicarboxamides possessing Structure I ( n = 5-8) revealed that these amides show strong association tendencies in very dilute solutions and suggested that further aggregation of associated amide molecules leads to micellization (2).…”
mentioning
confidence: 99%
“…The viscosities and partial molal volumes of aqueous solutions of tetramethylpimelamide have been reported recently (6). In continuing efforts to study its physicochemical properties, it was considered desirable to measure its dielectric constant and from the measured value calculate the dipole moment.…”
mentioning
confidence: 99%